Novel Approach for the Synthesis of Nanocrystalline Anatase Titania and Their Photovoltaic Application. (9th October 2011) - Srinivasu, Pavuluri; Singh, Surya Prakash; Islam, Ashraful; Han, Liyuan
Abstract : High surface area titania with crystalline anatase walls has been synthesized using ordered large mesoporous carbon as a template. The pore structure of mesoporous carbon is infiltrated with titanium tetraisopropoxide solution at room temperature and the mixture is subjected to heat treatment at550 C o in presence of air to complete removal of the template. The prepared crystalline anatase frameworks are characterized by XRD, N2 adsorption and HR-TEM. The nitrogen adsorption-desorption analysis of the prepared anatase titania particles exhibits BET specific surface area of 28 m 2 /g. The dye-sensitized solar cells performance of this anatase titania material has been tested and energy conversion efficiency of 3.0% is achieved under AM 1.5 sunlight. This work reports a new approach for fabrication of nanocrystalline anatase titania by simple hard templating technique for the first time and their applications for dye-sensitized solar cell.